EARLY JOB ADAPTATION CHALLENGES OF NEW EMPLOYEES IN TAIWAN’S HARDWARE RETAIL SECTOR - Pei-Rong Lu, (PEOPLE: International Journal of Social Sciences, 2026)
Amid ongoing labor shortages, employee retention has become a critical concern for organizations. This study explores the early job adaptation challenges experienced by new employees during their first one to three months of employment. Focusing on a hardware retail company in Taiwan, this study employed a qualitative case study approach based on semi-structured interviews with 36 employees, including full-time staff and interns. The findings reveal three major categories of adaptation challenges: insufficient professional knowledge, interpersonal relationship difficulties, and adjustment to workplace pace. Among these, inadequate professional knowledge emerged as the most significant issue, particularly regarding product knowledge, professional terminology, and customer communication skills. Over 70% of participants identified this factor as their primary adaptation challenge. The findings highlight the importance of practical training and workplace support mechanisms in facilitating newcomer adaptation and improving employee retention in labor-intensive retail environments. This study contributes to the understanding of early-stage employee adaptation in the retail sector and offers practical implications for human resource management.